Prime Minister Julia Gillard presenting novelist Melina Marchetta with her award at the Prime Minister's Literary Awards held at the National Library of Australia, Canberra, 8 July 2011 - Mackenzie, Craig, 1969-; National Library of Australia (Canberra : National Library of Australia, 2011)
Melina Marchetta accepting her award for being shortlisted in the young adult fiction category for her novel 'The Piper's Son'.
Title devised by cataloguer based on information from acquisitions documentation.
Part of the collection: Prime Minister's Literary Awards held at the National Library of Australia, Canberra, 8 July 2011.
Acquired in digital format; access copy available online.
Mode of access: Internet via World Wide Web.
Photographed by the National Library's photographers, Craig Mackenzie and Samuel Cooper.
Keywords: Gillard, Julia -- Portraits; Marchetta, Melina, -- 1965- -- Portraits; Women prime ministers -- Australia -- Portraits; Novelists, Australian -- Portraits; Literary prizes -- Australian Capital Territory -- Canberra -- Photographs; Prime ministers; Novelists